Editor's Note - Jimenez, Emmanuel; Revenga, Ana L. (Oxford University Press on behalf of the World Bank, 2014)
The lives of girls and women in developing countries have improved dramatically over the past quarter of a century. Female life expectancy at birth has increased dramatically to reach 71 years globally in 2007. Literacy rates have risen and in a third of developing countries there are more girls in secondary school than boys. Most strikingly, in more than half the developing countries more women attend university than men. Women have entered the labor force in massive numbers and now account for 40% of the global work force. Moreover, change has come much more quickly than it did historically in the rich countries.